Easy labeling of proliferative phase and sporogonic phase of microsporidia Nosema bombycis in host cells. - Jie Chen; Wei Guo; Xiaoqun Dang; Yukang Huang; Fangyan Liu; Xianzhi Meng; Yaoyao An; Mengxian Long; Jialing Bao; Zeyang Zhou; Zhonghuai Xiang; Guoqing Pan (PLoS ONE)
Microsporidia are eukaryotic, unicellular parasites that have been studied for more than 150 years. These organisms are extraordinary in their ability to invade a wide range of hosts including vertebrates and invertebrates, such as human and commercially important animals. A lack of appropriate labeling methods has limited the research of the cell cycle and protein locations in intracellular stages. In this report, an easy fluorescent labeling method has been developed to mark the proliferative and sporogonic phases of microsporidia Nosema bombycis in host cells. Based on the presence of chitin, Calcofluor White M2R was used to label the sporogonic phase, while β-tubulin antibody coupled with fluorescence secondary antibody were used to label the proliferative phase by immunofluorescence. This method is simple, efficient and can be used on both infected cells and tissue slices, providing a great potential application in microsporidia research.